CORPUS TOOLS AND SOFTWARE: OVERVIEW AND APPLICATIONS (Ustozlar uchun, 2025)
This article provides an overview of corpus tools and software used in modern linguistic research and language education. Corpus tools are specialized computer programs that enable the collection, organization, and analysis of large language datasets, known as corpora. The study also highlights how corpus software supports data-driven learning (DDL), allowing students and teachers to explore authentic examples of language use. Furthermore, it emphasizes the integration of corpus technology in computational linguistics and digital humanities, where automatic annotation, part-of-speech tagging, and keyword extraction contribute to understanding language variation, discourse, and cultural trends. By combining quantitative precision with qualitative interpretation, corpus tools have become indispensable instruments for both theoretical and applied linguistics, promoting evidence-based approaches to language study and pedagogy